Identification of customer satisfaction in services: a study on agribusiness dealers - Lütkemeyer Filho, Mario Gilberto; Roehe Vaccaro, Guilherme Luís; de Freitas, Ernani Cesar (Review of Business Management, 2015)
Objective – This paper presents an analysis of service factors that impact customer satisfaction with dealers in the sugarcane segment in Sao Paulo state – Brazil. Design/methodology/approach – The research method is descriptive quantitative, based on survey. Data is secondary gathered from the tractor-making company’s database, with n = 88. Tools used for multivariate statistical analysis were factor analysis and correspondence analysis. Findings – The results revealed a reduction in latent variables into two components: trust and relationship. The correspondence analysis presents association among variables “cost-benefit of spare parts” and “treated fairly and honestly”. Practical implications – Despite the evidence of a relationship between the results and the information available in the literature, results cannot be generalized, since theory doesn´t fully describes the investigated sector. Future research may advance towards validating if the emerged variables are relevant on the strategic decision making process for this segment.